Untold stories of Polish heroes from World War II - Ziółkowska-Boehm, Aleksandra 1949- (Hamilton Books, 2018)
In 1939, both Germany (September 1st) and Soviet Union (September 17) invaded Poland. The eight narratives presented in this book deal with Polish destinies, untold stories of people, mostly very young, who survived the Second World War, and how great an impact the war had on their lives. --Preface
Keywords: Zweiter Weltkrieg; Polen; World War (1939-1945); World War, 1939-1945 / History; World War, 1939-1945 / Poland; Poland / Biography; Poland; 1939-1945; Biography; History; Biografie